Controllable synthesis of mesoporous alumina with large surface area for high and fast fluoride removal. Issue 14 (1st November 2016) - Xu, Naicai; Liu, Zhong; Dong, Yaping; Hong, Tianzeng; Dang, Li; Li, Wu
Abstract: Gamma phase of mesoporous alumina (MA) with large surface area was successfully synthesized by a facile hydrothermal method followed by thermal treatment for fluoride removal. The as-synthesized MA nanoparticles with average size of 20 nm–150 nm have ordered wormhole-like mesoporous structure. The pore size is 5 nm with a narrow distribution, and the specific surface area reaches 357 m 2  g −1 while the bulk density is 0.45 cm 3  g −1 . Glucose as a small-molecule template plays an important role on the morphology, surface area and pore diameter of the MA. As an ionic adsorbent for fluoride removal, the maximum adsorption capacity of MA is 8.25 mg g −1, and the remove efficiency reaches 90% in several minutes at pH of 3. The Langmuir equilibrium model is found to be suitable for describing the fluoride sorption on MA and the adsorption behavior follows the pseudo-second-order equation well with a correlation coefficient larger than 0.99. The larger surface area and relatively narrow pore size of MA are believed to be responsible for improving the adsorption efficiency for fluoride in aqueous solution.